(untitled) (Homoeopathy for All, 2022)
Acidity is described in terms of the pH value of a substance. Acidity in the stomach refers to a set of symptoms caused by an imbalance between the acid secreting mechanism of the stomach and proximal intestine and the protective mechanisms that ensure their safety. Acid is secreted by parietal cells in the proximal two thirds (body) of the stomach. The pH of the acid ranges from 1.5 to3.5. This acid helps in breakingdown the food during digestion. Gastric acid aids digestion by creating the optimal pH for pepsin and gastric lipase and by stimulating pancreatic bicarbonate secretion. When there is excess production of acid by the gastric glands, it results in the condition known as acidity. Consumption of alcohol, highly spicy foodstuffs, non-vegetarian diets and non steroidal anti-inflammatory drugs(NSAIDs) also predispose to gastric acidity.